2009
DOI: 10.1021/ja906332r
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Detail Revealed via Comprehensive Kinetic Modeling of [rac-C2H4(1-indenyl)2ZrMe2]-Catalyzed 1-Hexene Polymerization

Abstract: Thorough kinetic characterization of single-site olefin polymerization catalysis requires comprehensive, quantitative kinetic modeling of a rich multiresponse data set that includes monomer consumption, molecular weight distributions (MWDs), end group analysis, etc. at various conditions. Herein we report the results obtained via a comprehensive, quantitative kinetic modeling of all chemical species in the batch polymerization of 1-hexene by rac-C(2)H(4)(1-Ind)(2)ZrMe(2) activated with B(C(6)F(5))(3). While ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
90
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(92 citation statements)
references
References 46 publications
2
90
0
Order By: Relevance
“…In many studies the kinetic parameters of the olefin insertion into the metal–carbon bond are determined 1115. Nevertheless, to the best of our knowledge, the activation enthalpy (Δ H ≠ ) and entropy (Δ S ≠ ) values have never been reported for the same catalytic system featuring the two most frequently used counterions, that is, the “sticky” MeB(C 6 F 5 ) 3 − and the weakly coordinating B(C 6 F 5 ) 4 − anion.…”
Section: Methodsmentioning
confidence: 99%
“…In many studies the kinetic parameters of the olefin insertion into the metal–carbon bond are determined 1115. Nevertheless, to the best of our knowledge, the activation enthalpy (Δ H ≠ ) and entropy (Δ S ≠ ) values have never been reported for the same catalytic system featuring the two most frequently used counterions, that is, the “sticky” MeB(C 6 F 5 ) 3 − and the weakly coordinating B(C 6 F 5 ) 4 − anion.…”
Section: Methodsmentioning
confidence: 99%
“…Typical steps that can be embedded into such a model are chain transfer (to monomer, H2, AlR3…), β-H elimination with differentiation between vinyl and vinylidene chain-ends formation, misinsertions (i.e., regioirregular insertions) of the -olefin monomer, restitution after these misinsertions (i.e., reactivation of a dormant chain), etc. An example of a comprehensive model involving up to 12 elementary processes is delineated in Scheme 2 [35].…”
Section: First-principles Kinetic Modellingmentioning
confidence: 99%
“…It is evident that kinetic studies based on direct measurement of the active center concentration in the polymerization system can lead to easier construction of a comprehensive mechanistic model. Many such studies have been reported based on various methods of counting the active center in metallocene catalysts . In most of the literatures, the determined active center ratios ([C * ]/[Mt], where [Mt] is concentration of the metallocene complex) in homogeneous metallocene catalysis systems were evidently lower than 1, meaning that only a part of the metallocene complex could be turned to active center.…”
Section: Introductionmentioning
confidence: 99%